Răspuns :
{ [ ( a × 2 - 19 ) : 9 + 1 ] × 23 } : 2 = 115
{ [ ( a × 2 - 19 ) : 9 + 1 ] × 23 } = 115 × 2
{ [ ( a × 2 - 19 ) : 9 + 1 ] × 23 } = 230
[ ( a × 2 - 19 ) : 9 + 1 ] = 230 : 23
[ ( a × 2 - 19 ) : 9 + 1 ] = 10
( a × 2 - 19 ) : 9 = 10 - 1
( a × 2 - 19 ) : 9 = 9
a × 2 - 19 = 9 × 9
a × 2 - 19 = 81
a × 2 = 81 + 19
a × 2 = 100
a = 100 : 2
a = 50
{ [ ( a × 2 - 19 ) : 9 + 1 ] × 23 } = 115 × 2
{ [ ( a × 2 - 19 ) : 9 + 1 ] × 23 } = 230
[ ( a × 2 - 19 ) : 9 + 1 ] = 230 : 23
[ ( a × 2 - 19 ) : 9 + 1 ] = 10
( a × 2 - 19 ) : 9 = 10 - 1
( a × 2 - 19 ) : 9 = 9
a × 2 - 19 = 9 × 9
a × 2 - 19 = 81
a × 2 = 81 + 19
a × 2 = 100
a = 100 : 2
a = 50
Răspuns:
Explicație pas cu pas:
{ [(a x 2) -19] : 9 +1 } x 23 : 2 = 115
Se rezolva pornind de la final prin operatii inverse :
115 x2 = 230
{ [(a x 2) -19] : 9 +1 } x 23 = 230
apoi 230: 23 =10
{ [(a x 2) -19] : 9 +1 } = 10
10 - 1 = 9
[(a x 2) -19] : 9 = 9
9x9= 81
[(a x 2) -19] = 81
81 + 19 = 100
(a x 2) = 100
a = 100 : 2
a= 50